Potential of avocado seed ethanol extract (Persea americana Mill. var Miki) as an anti-aging - Alya, Syadza; Hasballah, Kartini; Fitria, Fitria; Harnelly, Essy; Sary, Nirwana Lazuardi (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Skin aging, characterized by decreased skin elasticity, is a global concern closely related to elastin degradation caused by oxidative stress and elastase activity. Natural ingredients rich in antioxidants are increasingly explored as potential anti-aging agents. Avocado (Persea americana) seeds contain various bioactive compounds that may protect elastin and slow the skin aging process. This study employed in silico and in vitro approaches to evaluate the antioxidant and anti-elastase activities of ethanol extract of avocado seeds from Bener Meriah, Aceh. Extraction was performed using maceration with 70% ethanol, followed by phytochemical screening. Antioxidant activity was assessed using the DPPH method. Anti-elastase activity was evaluated in silico through molecular docking against porcine pancreatic elastase (PPE) and in vitro using the SANA substrate and PPE enzyme. The avocado seed ethanol extract showed strong antioxidant activity with an IC₅₀ value of 47.31 ppm. It also demonstrated potent anti-elastase activity with an IC₅₀ value of 6.980 ppm. Molecular docking revealed that cholestan-3-ol, 2-methylene-, (3β,5α)- had a binding affinity of −8.0 kcal/mol, comparable to the control. Overall, the ethanol extract of avocado seeds exhibits very strong antioxidant and significant anti-elastase activities both in silico and in vitro, indicating its potential as a natural anti-aging agent.